Years of healthy life lost due to adverse pregnancy and childbirth outcomes among adolescent mothers in Thailand - Ei Ei Aung; Tippawan Liabsuetrakul; Warisa Panichkriangkrai; Nuttapat Makka; Kanitta Bundhamchareon (AIMS Press, 2019)
Background: Preventing adolescent pregnancy and childbirth is one of the targets of Sustainable Development Goals. Measuring the burden pregnancy and childbirth places on adolescents is required to convince society and decision makers that this is an important goal. Objective: This study aimed to estimate (1) the years of healthy life lost due to adolescent pregnancy and childbirth in terms of disability adjusted life years (DALYs), (2) the contribution of adolescent pregnancy and childbirth to the total DALYs lost from all reproductive ages, and (3) the magnitude of the burden due to five main direct obstetric causes and sequelae in adolescent mothers in Thailand in 2014. Methods: Data were retrieved from a national in-patient registered database and a vital registration database. Health consequences of five main direct obstetric causes were extracted from the Global Burden of Diseases (GBD) 2000 study. The DALYs were calculated by the combination of Years of Life Lost (YLL) due to premature death and Years Lived with Disability (YLD) due to adverse pregnancy and childbirth in adolescent mothers. Results: There were a total of 2599 years of DALYs lost from the consequences of adolescent pregnancy and childbirth, and unsafe abortion resulted in the highest burden. Mortality was the primary driver for the total DALYs lost with 1704 years, and maternal hemorrhage dominated in the total YLL. Unsafe abortion contributed the highest burden to nonfatal morbidity. Obstructed labor commonly occurred in adolescent pregnancies. Conclusion: Among the DALYs lost due to pregnancy and childbirth for all reproductive aged women, 15.4% were attributed to adolescents. The five main obstetric causes of mortality and morbidity are all preventable conditions. Increased efforts from all stakeholders are essential to implement appropriate interventions to minimize adverse health outcomes in adolescent mothers.